The Assembly of the Mixture of Two Ionic Surfactants in Polyols Media at Variable Temperatures: Combined Conductivity and Theoretical Investigations. Issue 1 (22nd June 2021) - Alam, Md. Masud; Mahbub, Shamim; Alfakeer, M.; Hoque, Md. Anamul; Mustafa, Syed Khalid; Ahmad, M. Ayaz; Kabir, Shariff E.
Abstract: Herein, the aggregation phenomena of the two cationic amphiphiles, the hexadecyltrimethylammonium bromide (CTAB), and tetradecyltrimethylammonium bromide (TTAB), has been investigated in the presence of monosaccharide (glucose) and disaccharide (maltose) at varying compositions and temperatures. The critical micelle concentration ( cmc ), degree of ionization ( g ), and several thermodynamic properties have been estimated applying the conductivity measurement technique. To explore the consequence of additives on the mixed micellization of TTAB + CTAB, glucose as monosaccharide having two concentrations (1% & 5% ( w/w ) glucose) and maltose as disaccharide containing single concentration (1% ( w/w )) have been employed. Together with the mixture of TTAB and CTAB, investigation of the physicochemical parameters of pure amphiphiles in glucose and maltose solutions was quantified. The efficiency of the additives in depressing the cmc values followed the order: 1 ( w/w ) % maltose >5 ( w/w ) % glucose >1% ( w/w ) glucose. The ideal cmc ( cmc id ), activity coefficients, and β values suggested the synergistic attraction (attractive force) between these two surfactants. By utilizing the Rubingh model, the evaluated micellar mole fractions of CTAB ( α 1 ) coupled with the ideal mole fraction ( X 1 id ) imply the increase of the contribution of CTAB in the mixed micellization with rising the α 1 values. The values of the negative excess free energy ( Δ G ex Rub ) implied the stability of the mixed micelle formed. The changes in standard enthalpy (Δ H° m ) and changes in standard entropy ( ΔS° m ) of micellization reveal the presence of different modes of interactions like electrostatic, ion‐dipole, H‐bonding, and hydrophobic interactions among the studied components.